Bacterial cyanide degradation is under review: Pseudomonas pseudoalcaligenes CECT5344, a case of an alkaliphilic cyanotroph. (19th January 2011) - Luque-Almagro, Victor M.; Blasco, Rafael; Martínez-Luque, Manuel; Moreno-Vivián, Conrado; Castillo, Francisco; Roldán, M. Dolores
Abstract : There are thousands of areas in the U.S.A. and Europe contaminated with cyanide-containing wastes as a consequence of a large number of industrial activities such as gold mining, steel and aluminium manufacturing, electroplating and nitrile pesticides used in agriculture. Chemical treatments to remove cyanide are expensive and generate other toxic products. By contrast, cyanide biodegradation constitutes an appropriate alternative treatment. In the present review we provide an overview of how cells deal in the presence of the poison cyanide that irreversible binds to metals causing, among other things, iron-deprivation conditions outside the cell and metalloenzymes inhibition inside the cell. In this sense, several systems must be present in a cyanotrophic organism, including a siderophore-based acquisition mechanism, a cyanide-insensitive respiratory system and a cyanide degradation/assimilation pathway. The alkaliphilic autochthonous bacterium Pseudomonas pseudocaligenes CECT5344 presents all these requirements with the production of siderophores, a cyanide-insensitive bd -related cytochrome [Cio (cyanide-insensitive oxidase)] and a cyanide assimilation pathway that generates ammonium, which is further incorporated into organic nitrogen.